Identification of a truncated form of the nerve growth factor receptor. - DiStefano, P S (1988)
Schwann cells express growth factor (NGF) receptors on their cell surface in response to axotomy, a phenomenon that can be demonstrated both in vivo and in vitro. The predominant form of the NGF receptor on Schwann cells exists as an approximately equal to 80-kDa band, as determined by NaDodSO4/PAGE. We demonstrate that cultured Schwann cells shed a truncated (50-kDa) form of the NGF receptor (NGF-Rt) into their medium. Other cell types that shed the NGF-Rt into medium include a rat schwannoma and, to a lesser extent, PC12 cells and superior cervical ganglion neurons. NGF-Rt was not found in media conditioned by mixed neuron/glia cultures from various brain regions, or anterior pituitary cells derived from rat. In vivo, NGF-Rt was present in neonatal rat urine, and its presence was developmentally regulated: levels were high in postnatal day-1 rat urine and declined to low, but detectable, levels by weeks 4 and 8. NGF-Rt was also found in amniotic fluid and in the stomach contents of fetal rats. Maternal urine (pre- and postnatal) had slightly elevated NGF-Rt levels over normal adult urine. NGF-Rt was detected in rat plasma and showed developmental regulation similar to that found for urine. In addition, a 77-kDa receptor species was detected in plasma during early development. Finally, NGF-Rt was significantly elevated in the urine of adult rats with bilateral sciatic nerve lesions. These findings suggest that the developmentally regulated release of NGF-Rt, present in plasma and other body fluids, plays a regulatory role in nervous system development.